Transforming urban economies - Colantonio, Andrea (LSE cities., 2013)
Cities house the majority of the world's population and are the dynamic centres of 21st century life, at the heart of economic, social and environmental change. They are still beset by difficult problems but often demonstrate resilience in the face of regional and national economic decline. Faced by the combined threats of globalisation and world recession, cities and their metropolitan regions have had to fight hard to maintain their global competitiveness and protect the quality of life of urban residentsTransforming Urban Economies: Policy Lessons from Europea.